2022
DOI: 10.3389/fimmu.2021.730666
|View full text |Cite
|
Sign up to set email alerts
|

Toripalimab: the First Domestic Anti-Tumor PD-1 Antibody in China

Abstract: Toripalimab (Tuoyi™) is a selective, recombinant, humanized monoclonal antibody against programmed death protein 1 (PD-1) developed by Shanghai Junshi Bioscience Co., Ltd. Toripalimab is able to bind to PD-1 and block the interaction with its ligands. The binding of toripalimab to PD-1 is mainly attributed to the heavy chain of the former and the FG loop of the latter. Toripalimab received a conditional approval in China for the treatment of melanoma (second-line) in December, 2018. It has also received approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 120 publications
4
37
0
Order By: Relevance
“…Toripalimab, a PD-1 inhibitor, has been approved for the treatment of NPC, esophageal carcinoma, melanoma, and soft tissue sarcoma in China [ 16 ]. Here, we report the results of a phase Ib clinical trial that investigated the safety and efficacy of neoadjuvant toripalimab combined with GP in resectable locally advanced HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Toripalimab, a PD-1 inhibitor, has been approved for the treatment of NPC, esophageal carcinoma, melanoma, and soft tissue sarcoma in China [ 16 ]. Here, we report the results of a phase Ib clinical trial that investigated the safety and efficacy of neoadjuvant toripalimab combined with GP in resectable locally advanced HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other PD-1 inhibitors, it binds to the FG loop of the PD-1 receptor identified via unconventional three-dimensional structure analysis. 25 Increasing studies have shown that Toripalimab alone or combined with chemotherapy exhibits promising effects and favourable tolerability in various malignancies and the adverse reactions to Toripalimab are acceptable and generally manageable. 26,27 In recent years, an evergrowing number of efforts have been made to explore chemo-immunotherapy, with encouraging results in its ability to overcome primary resistance to PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Immune-related cystitis may be suspected in patients treated with ICI who develop symptoms of urinary tract irritation (such as dysuria, pollakiuria, or urinary urgency), leukocyturia or erythrocyturia in urine samples, and after infective etiologies have been ruled out by consecutive urinary cultures or antibiotic failure. We have found eight cases described in the literature [ 219 ] in patients receiving pembrolizumab, nivolumab, and to-ripalimab (a monoclonal anti PD-1 antibody approved in China [ 220 ]). Using data from the FDA adverse database, 19 reports were identified by He et al [ 219 ].…”
Section: Methodsmentioning
confidence: 99%